AN INCLUSIVE PERSPECTIVE ON THE MANAGEMENT OF SERVICE INSTITUTIONS ALONG GLOBAL RISK IN THE CONTEXT OF OVERCOMING THE GLOBAL FINANCIAL CRISIS - Melnychuk , Yu. M. (The actual problems of regional economy development, 2023)
The article "Аn inclusive perspective on the management of service institutions along global risk in the context of overcoming the global financial crisis" is dedicated to the main inclusive areas of overcoming financial risks that arose during the Covid-19 pandemic. The article examines the importance and necessity of the hotel business in the cultural, social and economic spheres of the country and the world. There is a parallel between the development of the hotel business and the crisis pandemic in the country. The problems that arose during the pandemic, the threats to business, the consequences that led to financial losses are highlighted. The practical inclusive experience of the world's leading hotel companies was taken into account. The economic factors affecting the state of the hotel business and the ways to overcome them have been studied. Structured management proposals for overcoming financial crises, overcoming existing situations, and ways to prevent them are provided. The work used a set of research methods that constitute the methodology of analysis and organization of the main publications, legislative acts and laws, namely the methods of generalization, comparison, chronology, analysis and generalization. A feature of the study was the use of the "Petal" histogram to display the digital impact of the Covid-19 pandemic on the level of revenue from hotel services. The article deals with the urgent issue of saving the hotel business in the period of global crises. The task of researching the management of service institutions during the Covid-19 pandemic in the context of overcoming the global financial crisis has been solved. The world experience of solving problems and inclusive experience in atypical situations that arise when global crises, namely Covid-19, are used. The totality of factors influencing the activity of the hotel enterprise was studied, and a systematic division into internal and external was carried out. It is explained that the external environment of the organization is a set of elements that are not part of the organization, but have a certain influence on it; to external factors affecting the activity of hotel enterprises: suppliers, inflationary processes in the country, consumers, the legislation of the country, competitors, adjacent markets. The problem of recovery and business development of enterprises in the tourism and hospitality industry in modern conditions complicated by the Covid-19 pandemic has been identified. Close cooperation and consolidated activities between enterprises of the industry, search for inclusive ways of cooperation, one of which is the creation of combined hotels, are proposed. This form of cooperation in the hospitality industry increases the competitiveness of enterprises in this field, allows closing and restoring medium and large small business enterprises, and ensures their further development at the national level.